Nanolipid-Trehalose Conjugates and Nano-Assemblies as Putative Autophagy Inducers - Eleonora Colombo; Michele Biocotino; Giulia Frapporti; Pietro Randazzo; Michael S. Christodoulou; Giovanni Piccoli; Laura Polito; Pierfausto Seneci; Daniele Passarella (MDPI AG, 2019)
The disaccharide trehalose is an autophagy inducer, but its pharmacological application is severely limited by its poor pharmacokinetics properties. Thus, trehalose was coupled via suitable spacers with squalene (in 1:2 and 1:1 stoichiometry) and with betulinic acid (1:2 stoichiometry), in order to yield the corresponding nanolipid-trehalose conjugates 1-Sq-mono, 2-Sq-bis and 3-Be-mono. The conjugates were assembled to produce the corresponding nano-assemblies (NAs) Sq-NA1, Sq-NA2 and Be-NA3. The synthetic and assembly protocols are described in detail. The resulting NAs were characterized in terms of loading and structure, and tested in vitro for their capability to induce autophagy. Our results are presented and thoroughly commented upon.